The threat to climate change mitigation posed by the abundance of fossil fuels. (7th February 2019) - Johnsson, Filip; Kjärstad, Jan; Rootzén, Johan
ABSTRACT: This article analyses the trends in primary demand for fossil fuels and renewables, comparing regions with large and small domestic fossil fuel reserves. We focus on countries that hold 80% of global fossil fuel reserves and compare them with key countries that have meagre fossil fuel reserves. We show that those countries with large domestic fossil fuel reserves have experienced a large increase in primary energy demand from fossil fuels, but only a moderate or no increase in primary energy from renewables, and in particular from non-hydro renewable energy sources (NHRES), which are assumed to represent the cornerstone of the future transformation of the global energy system. This implies a tremendous threat to climate change mitigation, with only two principal mitigation options for fossil-fuel-rich economies if there is to be compliance with the temperature goals of the Paris Agreement: (1) leave the fossil fuels in the ground; and (2) apply carbon capture and storage (CCS) technologies. Combinations of these two options to exploit their respective possibilities synergistically will require strong initiatives and incentives to transform a certain amount of the domestic fossil fuel reserves (including the associated infrastructure) into stranded assets and to create an extensive CCS infrastructure. Our conclusion is that immediate and disruptive changes to the use of fossil fuels and investments in non-carbon-emitting technologies are required if global warming is to be limited to well below 2°C. Collective actions along value chains in business to divert from fossil fuels may be a feasible strategy. Key policy insights The main obstacle to compliance with any reasonable warming target is the abundance of fossil fuels, which has maintained and increased momentum towards new fossil-fuelled processes. So far, there has been no increase in the share of NHRES in total global primary energy demand, with a clear decline in the NHRES share in India and China. There is an immediate need for the global community to develop fossil fuel strategies and policies. Policies must account for the global trade flow of products that typically occurs from the newly industrialized fossil fuel-rich countries to the developed countries.